KELIMPAHAN SERANGGA MUSUH ALAMI DAN SERANGGA HAMA PADA EKOSISTEM TANAMAN CABAI MERAH (Capsicum annum L.) PADA FASE VEGETATIF DI KECAMATAN DAU KABUPATEN MALANG - Zakeus Candra Jaya Kristiaga; Sutoyo; I Made Indra Agastya (Politeknik Negeri Lampung., 2020)
Pests are plant pests that cause damage to plants and generally originate from insects One of the obstacles in crop management is insect pests. The more associations that occur between insects and plants can potentially be detrimental to crop yields Insects also have the largest number of all species on this earth, have various roles and their existence is everywhere, apart from that insects can be attracted to plants both for food and as a place to live, so that insects are very important in the ecosystem and human life. Many insects are associated with chili plants, both as harmful insect pests and beneficial natural enemy insects, and some insects are useful as flower pollinators and destroyers of organic matter. The purpose of this study was to identify and identify insects that have potential as pests and natural enemies associated with red chili plants in the vegetative phase. This research was conducted from January to March 2020. In Landung Sari Dau with a height of 600 meters above sea level, and further identification was carried out at the Laboratory of Soil Science and Agronomy, University of Tribhuwana Tunggadewi Malang using a binocular microscope with a 10x magnifying lens. Based on the results of research and observations made from January to March. Eight orders were found in chili plants in the garden area of Malang Regency which was found in each trap, namely the Order of Coleoptera (Beetles), Order of Diptera (Flies), Order of Hymenoptera (Bees), Order of Hemiptera (Ladybugs), Order of Isoptera (Laron), Order of Lepidoptera (Kupu - Butterflies and Moths) Order of Odonata (Dragonflies), Order of Orthoptera (Grasshoppers and Crickets), with 861 individuals of which 729 are potential pests and 132 as natural enemies. The relative abundance of insects as pests was 84.67 %, while the abundance of insects as natural enemies was 15,33 %.